P247 Lumacaftor/ivacaftor is associated with high discontinuation rates in patients with baseline severe lung function but also benefits in those who tolerate therapy. (15th November 2017) - Wareham, JM; Webb, KA; Jones, AM; Brennan, AL; Bright-Thomas, RJ; Horsley, AR; Barry, PJ
Abstract : Lumacaftor/ivacaftor (LUM/IVA) is a combination CFTR modulator which is licensed for patients with cystic fibrosis homozygous for the Phe508del mutation. In clinical trials, use of LUM/IVA resulted in modest improvements in lung function, a reduction in pulmonary exacerbations and small increases in nutritional parameters. Although these trials excluded patients with FEV1 <40%, licensing does not restrict therapy on this basis. In the UK, LUM/IVA is only available on a managed access programme for patients with low lung function. We aimed to examine the safety, tolerability and effectiveness of LUM/IVA in patients with severe lung disease. 32 patients were admitted to commence LUM/IVA and 8 (25%) permanently discontinued therapy. One patient successfully recommenced therapy after discontinuation. Adverse event rate was 88%, with 87% related to respiratory symptoms. Therapy initiation was associated with significant relative falls in both FEV1 (−14±11.6%) and FVC (−11.6±13.1%) at 24 hours. A significant increase in CRP (mg/L) was identified at both day 3 [ 18 (7 -40) p<0.001] and day 7 [16.5 (5–49), p=0.038] compared to baseline [7.5 (4–18.8)]. Those patients who discontinued therapy had a higher increase in CRP at day 3 (p=0.01), a lower baseline pO2 (p=0.013) in the preceding year, and were more likely to complain of dyspnoea (p=0.017). For those who continued therapy, FEV1 increased compared to day 0 values (32.0%±6.9% v. 29.5%±6.7%, p=0.01) but not compared to best FEV1 in the preceding 3 months (31.1%±6.5%, p=0.23). A 2 kg increase in weight from day 0 was identified in those who continued LUM/IVA (p<0.001). In 14 patients who had at least 6 months therapy there was a reduction in the annualised rate of pulmonary exacerbations requiring iv antibiotics compared to the preceding year (3.2±2.8 v. 5.2±2.5, p=0.001) and days on iv antibiotics (47±33 v. 69±39, p=0.026). We report a very high adverse events rate associated with the initiation of LUM/IVA which was associated with adverse changes in objective markers. In those who tolerate therapy benefits may be similar to those reported in clinical trials.